The impact of social-emotional learning: A meta-analysis in China - Chen, Huan; Yu, Yanni (Frontiers in Psychology, 2022)
The cross-cultural adaptation of social-emotional learning (SEL) has cast doubts. Although there are significant differences between low-context and high-context cultures, few analyses have been conducted on the effects of SEL intervention in high-context cultures. To explore the effectiveness of the SEL program in China, which is different from low-context cultural background, this study presents findings from a meta-analysis of 86 randomized SEL programs involving 8736 students. Compared with the control group, SEL participants significantly improved social-emotional competence (SEC), including SEL skills, attitudes, positive social behavior, and emotional distress (reduction). However, there was no significant improvement in behavioral problems. Due to the lack of emotional education in China and the Hawthorne effect, compared with SEL programs in low-context countries, China's SEL programs have improved SEC more, up to 3 times that of low-context countries. The general area of the school, SEL framework, intervention object, and educational level of participants moderates SEL positive outcomes. Types of textbooks, SEL framework, participant features, and educational level of participants moderate SEL negative outcomes. These findings provide empirical evidence for the positive impact of SEL programs in China. To improve the SEC of Chinese students, policymakers should actively implement SEL programs in China.